2009
DOI: 10.1002/humu.20935
|View full text |Cite
|
Sign up to set email alerts
|

Mutational, functional, and expression studies of theTCF4gene in Pitt-Hopkins syndrome

Abstract: Pitt-Hopkins syndrome is a severe congenital encephalopathy recently ascribed to de novo heterozygous TCF4 gene mutations. We report a series of 13 novel PHS cases with a TCF4 mutation and show that EEG, brain magnetic resonance imagain (MRI), and immunological investigations provide valuable additional clues to the diagnosis. We confirm a mutational hot spot in the basic domain of the E-protein. Functional studies illustrate that heterodimerisation of mutant TCF4 proteins with a tissue-specific transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
205
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(214 citation statements)
references
References 26 publications
(28 reference statements)
6
205
1
2
Order By: Relevance
“…Tcf4 expression is sustained particularly in areas of high neuronal plasticity such as the cerebral cortex, hippocampus and cerebellum [13,112]. Human TCF4 expression has been detected in the prosencephalon and the ventricular zone of the embryonic CNS [133], in the telencephalon at all stages of fetal development as well as in the adult forebrain (http://www.brainspan.org/). In summary, TCF4 is the only E-protein being expressed at all stages in the developing and adult mouse and human brain.…”
Section: Tcf4/tcf4 Expression In Brain Developmentmentioning
confidence: 99%
“…Tcf4 expression is sustained particularly in areas of high neuronal plasticity such as the cerebral cortex, hippocampus and cerebellum [13,112]. Human TCF4 expression has been detected in the prosencephalon and the ventricular zone of the embryonic CNS [133], in the telencephalon at all stages of fetal development as well as in the adult forebrain (http://www.brainspan.org/). In summary, TCF4 is the only E-protein being expressed at all stages in the developing and adult mouse and human brain.…”
Section: Tcf4/tcf4 Expression In Brain Developmentmentioning
confidence: 99%
“…All mutations that cause PTHS are thought to result in haploinsufficiency of TCF4, consistent with the disorder being inherited in an autosomal dominant manner [62,63,67]. The majority of PTHS-associated missense mutations appear to attenuate transcriptional activity in reporter-based assays of gene function and also may impair heterodimer formation with other bHLH transcription factors [36,37,63,68].…”
Section: Pitt-hopkins Syndrome and Intellectual Disabilitymentioning
confidence: 96%
“…Intriguingly, TCF4-B has also been found to be a transcriptional repressor in different cell types [33][34][35]. However, it has been demonstrated that this isoform can also activate transcription in vitro, and therefore its function is highly context-dependent [30,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an interaction of TCF4 and MATH1, a proneural protein, on different neural progenitor populations was investigated and disrupted pontine nucleus development was found in TCF4 knock out mice. Second, several studies showed that TCF4 haploinsufficiency contributes to severe neurodevelopmental disorders such as the Pitt-Hopkins syndrome [1,4,9,33,40]. This autosomal dominant encephalopathy is characterized by severe mental retardation, microcephaly, disrupted motor development, and hyperventilation, as described above [25].…”
Section: Tcf4 and Cognitive Endophenotypes Of Schizophreniamentioning
confidence: 97%